Waris dalam Tinjauan Keadilan dan Kemanfaatan Q.S. al-Nisā’ Ayat 11-12 Perspektif Amina Wadud - Sama’un, Sama’un; Bahrudin, Ahmad (Lembaga Pengembangan Kinerja Dosen, 2025)
In inheritance law, the Qur’an typically stipulates a 2:1 distribution, where men receive two parts and women one. This division is often justified by the idea that men are responsible for earning a living, with women not typically involved in financial support. However, feminist exegete Amina Wadud argues that this distribution is not based on justice. She emphasizes that the primary consideration in inheritance should be the benefits the heirs will receive, rather than gender. This study aims to analyze inheritance distribution in Qs. al-Nisā’ verses 11-12 from Amina Wadud's feminist perspective, specifically her critique of the 2:1 ratio. The study is a qualitative library research study titled